2000
DOI: 10.1051/aas:2000211
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the dense gas between type 1 and type 2 Seyferts

Abstract: Abstract.We have used observations of the CO J = 1 → 0 transition in a sample of 20 Seyfert galaxies in order to test the result of Heckman et al. (1989), who find that type 2 Seyferts have a higher molecular gas content than type 1 Seyferts. From our observational results alone, we, when we use all of our sample (L FIR ∼ 10 10 − 10 11 L ). The results suggest that star-burst activity is most dominant in the (L FIR ∼ 10 10 L ) type 2 Seyferts, and the relative contribution of this activity to the FIR flux (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
(117 reference statements)
1
9
2
Order By: Relevance
“…Therefore, they concluded that the total amount of molecular gas is not responsible for the enhanced star-forming activity in Seyfert 2 hosts. Contrary to those observations, Heckman et al (1989) and Curran (2000), using observations of the CO J = 1-0 line, found that Sy2s do indeed have a higher molecular gas content than Seyfert 1s. Curran (2000) found that for Seyfert galaxies with far-infrared (FIR) luminosity (L FIR ) ≈ 10 10 L , the CO/FIR luminosity ratio in type 2 is at least three times that in type 1 sources.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Therefore, they concluded that the total amount of molecular gas is not responsible for the enhanced star-forming activity in Seyfert 2 hosts. Contrary to those observations, Heckman et al (1989) and Curran (2000), using observations of the CO J = 1-0 line, found that Sy2s do indeed have a higher molecular gas content than Seyfert 1s. Curran (2000) found that for Seyfert galaxies with far-infrared (FIR) luminosity (L FIR ) ≈ 10 10 L , the CO/FIR luminosity ratio in type 2 is at least three times that in type 1 sources.…”
Section: Introductioncontrasting
confidence: 75%
“…Contrary to those observations, Heckman et al (1989) and Curran (2000), using observations of the CO J = 1-0 line, found that Sy2s do indeed have a higher molecular gas content than Seyfert 1s. Curran (2000) found that for Seyfert galaxies with far-infrared (FIR) luminosity (L FIR ) ≈ 10 10 L , the CO/FIR luminosity ratio in type 2 is at least three times that in type 1 sources. They suggested that this molecular gas may be related in some indirect way to the nuclear material hypothesized to obscure the broad-line region in Sy2s.…”
Section: Introductioncontrasting
confidence: 75%
“…These results are in contrast with observations by Maiolino et al (1997), who have used the Harvard‐Smithsonian Center for Astrophysics (CfA) sample of active galaxies to compare the global CO emission from type 1 and type 2 Seyfert galaxies. They conclude that there is no significant difference between the CO emission of type 1 and 2 Seyfert galaxies, a result confirmed by the mean CO/FIR luminosity ratio being similar for the two Seyfert classes (Curran 2000). However, as noted by Curran, Aalto & Booth (2000), these samples are biased, due to only the distant galaxies having all of their CO sampled in the single pointings.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, for a given far-infrared luminosity, Lawrence & Elvis (1982) found a significant lack of soft X-ray emission in Seyfert 2 galaxies compared to Seyfert 1 galaxies (see also Mas-Hesse et al 1994;Cappi et al 1996) and Mas-Hesse et al (1994) found similar distributions of the hard X-ray emission for both kinds of Seyfert galaxies. Maiolino et al (1997) and Curran (2000) found no differences in the mean ratio of CO and far-infrared luminosity between the two Seyfert classes suggesting that both Seyfert types have the same amount of molecular gas. Morganti et al (1999) found that Seyfert 2 galaxies tend to have a larger projected radio linear size than Seyfert 1 galaxies, whereas there is no statistically significant difference in radio power between Seyfert 1 and Seyfert 2 galaxies.…”
Section: Introductionmentioning
confidence: 94%